The problem of the relations between the science and the subject-matter of education in the higher education of librarians and bibliographers - Renaldas Gudauskas (Knygotyra)
The subject-matter of education is one of the main elements of the didactic system. The correct determination of the main subject-matter of education enables the achievement of educational goals. Education and higher education are closely interconnected. However, one of the main problems in professional pedagogy—the relationship between science and the subject-matter of education—has not yet been fully resolved. This problem is particularly urgent in the training of skilled librarians and bibliographers because library and bibliography sciences are relatively young and rapidly developing.